MEMAHAMKAN KONSEP MATEMATIS SISWA KELAS IV SEKOLAH DASAR MELALUI LINTASAN KERETA BILANGAN - Hany Handayani; Ihsan Rizali; Asep Nurhuda; Atep Lesmana; Annisa Nurfitriani; Mubarok Somantri; Gemi Gustiani; Nadia Sunarti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by the low student learning outcomes in mathematics. This study aims to see the influence of the use of the Number Train Tracks media on the understanding of mathematical concepts in class IV elementary school students. This study used a quasi-experimental method with a Nonequivalent (Pretest and Posttest) Control-Group Design. The population in this study were fourth grade students at SDN 1 Jatiluhur and the samples were taken to fourth grade students as a control class (given conventional learning) of 24 students and fourth grade students as an experimental class (given the use of the Number Train Tracks media) as many as 24 students. Samples were taken using purposive sampling technique. Both the experimental class and the control class were given two tests, namely the Pretest and Posttest. The data collection technique used in this study was in the form of documentation and multiple choice tests of 15 questions which were declared valid. The data analysis technique used in this study is Mann- Whitney and N-Gain data which are preceded by normality tests and homogeneity tests. The research results obtained a significance value of 0.021 <0.05, then H1 is accepted. This means that there is an influence on the use of the Number Train Tracks media. From the N-Gain results, it was found that there was an increase in understanding of mathematical concepts with an average N-Gain in the experimental class of 52.79 in the high category and an average N-Gain in the control class of 36.33 in the medium category. Based on these results, there is an influence in increasing the understanding of mathematical concepts of students who are given learning media with Number Train Tracks better than classes with conventional learning.